Estimating the atmospheric properties of 44 M dwarfs from SPIRou spectra. Issue 3 (29th August 2022) - Cristofari, P I; Donati, J-F; Masseron, T; Fouqué, P; Moutou, C; Carmona, A; Artigau, E; Martioli, E; Hébrard, G; Gaidos, E; Delfosse, X
ABSTRACT: We describe advances on a method designed to derive accurate parameters of M dwarfs. Our analysis consists in comparing high-resolution infrared spectra acquired with the near-infrared spectro-polarimeter SPIRou to synthetic spectra computed from MARCS model atmospheres, in order to derive the effective temperature ( T eff ), surface gravity (log g ), metallicity ([M/H] ), and alpha-enhancement ([α /Fe] ) of 44 M dwarfs monitored within the SPIRou Legacy Survey (SLS). Relying on 12 of these stars, we calibrated our method by refining our selection of well-modelled stellar lines, and adjusted the line list parameters to improve the fit when necessary. Our retrieved T eff, log g, and [M/H] are in good agreement with literature values, with dispersions of the order of 50 K in T eff and 0.1 dex in log g and [M/H] . We report that fitting [α /Fe] has an impact on the derivation of the other stellar parameters, motivating us to extend our fitting procedure to this additional parameter. We find that our retrieved [α /Fe] are compatible with those expected from empirical relations derived in other studies.